CMTM3 inhibits cell migration and invasion and correlates with favorable prognosis in gastric cancer. Issue 1 (28th November 2013) - Su, Yu; Lin, Yi; Zhang, Lianhai; Liu, Baocai; Yuan, Wanqiong; Mo, Xiaoning; Wang, Xiaohong; Li, Henan; Xing, Xiaofang; Cheng, Xiaojing; Dong, Bin; Hu, Ying; et al.
<x xml:space="preserve">Abstract</x> The CKLF‐like MARVEL transmembrane domain containing 3 (CMTM3) gene is a novel tumor suppressor with frequent epigenetic inactivation. In this study, we showed the role played by CMTM3 in gastric cancer cells as a tumor suppressor gene, and examined the correlation between CMTM3 expression and clinicopathological parameters using immunohistochemistry in gastric cancer patients with different pathological stages (n = 350). We found that CMTM3 expression was reduced or silenced by epigenetic regulation in gastric cell lines, and dramatically downregulated in primary gastric cancer tissues. Restoration of CMTM3 significantly affected migration and invasion of AGS and SGC‐7901 cells (P < 0.001). In vivo experiments showed that peritoneal disseminated metastases were significantly suppressed by CMTM3 (P < 0.001). We further showed that the expression of MMP2 and the phosphorylation of Erk1/2 were decreased when CMTM3 was restored. In addition, by immunohistochemical staining, we found that the expression of CMTM3 was remarkably weaker in gastric cancer tissues than in normal mucosae (P = 0.008), and was significantly correlated with gender (P = 0.033), tumor depth (P = 0.049), stage (P = 0.021), and histological grade (P = 0.022). More importantly, CMTM3 expression was associated with prognosis in gastric cancer patients (P = 0.041), and was a significant independent prognostic indicator (hazard ratio = 0.704, 95% confidence interval, 0.498–0.994; P = 0.046). Our findings indicate that CMTM3 regulates migration and invasion of gastric cancer cells. Moreover, CMTM3 is a candidate marker for prognosis of gastric cancer in the clinic.